Mitochondrial DNA of Nellore and European x Nellore crossing cattle of high performance - Curi, Rogerio Abdallah [UNESP]; Mota, Lígia Souza Lima Silveira da [UNESP]; Silveira, Antonio Carlos [UNESP] (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 2007)
O objetivo deste trabalho foi avaliar, por meio de um polimorfismo no gene ND5 do DNA mitocondrial de bovinos, a porcentagem de indivíduos portadores de mtDNA Bos taurus indicus em animais Nelore PO (n = 69) e em animais provenientes do cruzamento entre machos europeus e fêmeas Nelore PO (n = 275). Apenas 2,26% (8/354) dos animais apresentaram mtDNA Bos taurus indicus. A alta freqüência de mtDNA Bos taurus taurus nesses animais pode ser reflexo de seleção, uma vez que os animais estudados se originam de linhagens selecionadas para alto desempenho de produção de carne.

The objective of this work was to evaluate, through a polymorphism in the ND5 gene of the bovine mitochondrial DNA, the frequency of Bos taurus indicus mtDNA individuals in a sample of Nellore purebred origin animals (n = 69) and crossbred animals originated from crosses of European sires and Nellore purebred origin females (n = 275). Only 2.26% (8/354) of the animals presented Bos taurus indicus mtDNA. The high frequency of Bos taurus taurus mtDNA in these animals can be a consequence of selection, once the animals studied are originated from selected lineages of high performance for meat production.
DNA mitocondrial de bovinos Nelore e cruzados Europeu x Nelore de alto desempenho
Keywords: Bos taurus indicus; Bos taurus taurus; gado de corte; polimorfismo de DNA; Bos taurus indicus; Bos taurus taurus; beef cattle; DNA polymorphism